2014
DOI: 10.1021/ol501509b
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Neutral α-Sulfenylation of Secondary Amines: Ring-Fused N,S-Acetals

Abstract: Secondary amines react with thiosalicylaldehydes in the presence of catalytic amounts of acetic acid to generate ring-fused N,S-acetals in redox-neutral fashion. A broad range of amines undergo α-sulfenylation, including challenging substrates such morpholine, thiomorpholine, and piperazines. Computational studies employing density functional theory indicate that acetic acid reduces the energy barriers of two separate steps, both of which involve proton transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 77 publications
1
27
0
Order By: Relevance
“…150 Das and Seidel reported C−P bond formation at the α position of nitrogen by a three-component reaction of pyrrolidine, aldehyde, and diphenylphosphine oxide 137 in the presence of 20 mol % benzoic acid (Scheme 50). 151 This redox-neutral reaction affords an efficient route to α-amino phosphine oxides 138, which are not readily available by the classic Kabachnik− Fields reactions.…”
Section: C−h Bond Functionalizationmentioning
confidence: 99%
“…150 Das and Seidel reported C−P bond formation at the α position of nitrogen by a three-component reaction of pyrrolidine, aldehyde, and diphenylphosphine oxide 137 in the presence of 20 mol % benzoic acid (Scheme 50). 151 This redox-neutral reaction affords an efficient route to α-amino phosphine oxides 138, which are not readily available by the classic Kabachnik− Fields reactions.…”
Section: C−h Bond Functionalizationmentioning
confidence: 99%
“…Seidel and co‐workers found that sulfenylation of secondary amines with thiosalicylaldehydes in the presence of catalytic amounts of acetic acid was possible. Various ring‐fused N,S‐acetals, found as key functional groups in pharmacologically active compounds, were obtained by this method . Computational studies employing density functional theory demonstrate that acetic acid could reduce the energy barriers of two separate steps (Scheme ).…”
Section: Thiols As Sulfenylation Reagentsmentioning
confidence: 99%
“…[39] This strategy was extended by the same group for the a-CAH sulfenylation of aliphatic amines. [40] Qu et al developed similar redox-neutral CAH oxygenation of pyrrolidine using 3,5-di-tert-butyl-o-benzoquinone. [41] During the optimization of the direct CAH oxygenation reaction, we observed that N-benzylated pyrrolidine 68 was formed in addition to the desired oxazine.…”
Section: Metal-and Oxidant-free Aryloxylationmentioning
confidence: 99%